1994
DOI: 10.1126/science.8009226
|View full text |Cite
|
Sign up to set email alerts
|

Receptor and Ligand Domains for Invasion of Erythrocytes by Plasmodium falciparum

Abstract: A 175-kilodalton erythrocyte binding protein, EBA-175, of the parasite Plasmodium falciparum mediates the invasion of erythrocytes. The erythrocyte receptor for EBA-175 is dependent on sialic acid. The domain of EBA-175 that binds erythrocytes was identified as region II with the use of truncated portions of EBA-175 expressed on COS cells. Region II, which contains a cysteine-rich motif, and native EBA-175 bind specifically to glycophorin A, but not to glycophorin B, on the erythrocyte membrane. Erythrocyte re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
467
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(497 citation statements)
references
References 21 publications
15
467
0
4
Order By: Relevance
“…3). As a further control for effective trypsin treatment, we demonstrated that trypsin-treated Kx null erythrocytes failed to bind to EBA-175 (data not shown), a parasite ligand for trypsin-sensitive glycophorin A (12).…”
Section: Resultsmentioning
confidence: 99%
“…3). As a further control for effective trypsin treatment, we demonstrated that trypsin-treated Kx null erythrocytes failed to bind to EBA-175 (data not shown), a parasite ligand for trypsin-sensitive glycophorin A (12).…”
Section: Resultsmentioning
confidence: 99%
“…The prototypic member of this family, P. falciparum EBA-175, was first identified as a soluble protein which appeared in in vitro culture supernatants after merozoite release and was shown to bind specifically to erythrocytes (Camus and Hadley, 1985). All the DBL-EBPs initially sequester in micronemes in the form of type I integral membrane proteins, probably mediate their function at invasion in a membrane-bound form at the parasite surface (Sim et al, 1994;Reed et al, 2000;Mayer et al, 2001;Duraisingh et al, 2003a;Maier et al, 2003), and are then shed via proteolytic cleavage to produce the soluble forms which accumulate extracellularly (Adams et al, 1990;Orlandi et al, 1990). Shedding of DBL-EBP and other ZSPs with an adhesive role may be integral to their function, constituting a means of ultimately removing them to allow the completion of invasion once they have performed their adhesive task in the invasion pathway.…”
Section: Why Shed?mentioning
confidence: 99%
“…Invasion phenotypes can be broadly classified into 2 main groups: (a) sialic acid-dependent (SA-dependent) invasion, demonstrated by poor invasion of neuraminidase-treated erythrocytes (neuraminidase cleaves SA on the erythrocyte surface); and (b) SA-independent invasion, demonstrated by efficient invasion of neuraminidasetreated erythrocytes. SA-dependent (neuraminidase-sensitive) invasion involves the 3 EBAs and PfRh1, with EBA175 probably being the most important (11,13,15,17,19,24,28,29). These ligands bind to SA on the erythrocyte surface.…”
Section: Introductionmentioning
confidence: 99%
“…These ligands bind to SA on the erythrocyte surface. EBA175 and EBA140 bind to glycophorin A (28)(29)(30) and C (13), respectively. EBA181 binds to SA on the erythrocyte surface and to band 4.1 protein (15,31).…”
Section: Introductionmentioning
confidence: 99%